Organizational leadership and succession practices for the spirited executives - Khaliq, Ahmad (Malaysian Institute of Management, 2018)
The Organizational Leadership is necessary and what is more if not equally important is a succession planning.This article focuses on the succession plan of early Islamic leaders Abu Bakr, Omar, Uthman and Ali (r.a.)who were trained by the Prophet himself and succeeded one after another. They demonstrated different leadership qualities. One thing was common among them that most of them were spiritually upright and set an example for modern corporate leaders to follow.